PEMBANGUNAN WEBSITE PENJUALAN BAJU CUSTOM PADA TOKO PROJECT7 - Willyam Jordan Kusuma (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
Custom clothing is an apparel product that is currently trending, because many people want clothes with different motifs, or with pictures on them. However, because of the large number of customers who want orders, a website is needed to ensure that there is stock of clothes that are sold or are out of stock at that time. This study aims to build a sales website. The Waterfall Model method or waterfall model is used in designing the sales website, the Waterfall method provides a sequential software lifecycle approach, starting from analysis, design, coding, testing, and supporting stages. The development of the sales website uses HTML and CSS programming languages. Data collection uses a Google form questionnaire containing questions with answers on a scale of